Electrochemical polishing electrolyte and electrochemical polishing method

By using an electrochemical polishing electrolyte and method, combined with electrolytes, corrosion inhibitors and additives, the problem of "frame mark" after anodizing of forged aluminum materials was solved, and the gloss and uniformity of the aluminum surface were improved, making it suitable for mass production.

CN121065803APending Publication Date: 2025-12-05LUXCASE PRECISION TECH (YANCHENG) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511217117.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-28
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

Existing technologies are insufficient to effectively address the "frame mark" defect that appears on forged aluminum materials after anodizing. Traditional chemical polishing processes easily expose microscopic defects, and existing electrochemical polishing solutions struggle to precisely control the amount of corrosion.

Method used

An electrochemical polishing electrolyte containing electrolytes, corrosion inhibitors, and additives is used. By precisely controlling the amount of corrosion and combining it with appropriate bias voltage and temperature, uniform corrosion and surface gloss are achieved.

Benefits of technology

It effectively improves the "frame print" defect, enhances the gloss and uniformity of the aluminum surface, and is suitable for large-scale application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121065803A_ABST
    Figure CN121065803A_ABST
Patent Text Reader

Abstract

The invention provides an electrochemical polishing electrolyte and an electrochemical polishing method, the electrochemical polishing electrolyte comprises an electrolyte, a corrosion inhibitor, an additive and a solvent, and the additive comprises any one or a combination of at least two of ethylene glycol, saccharin, sodium nitrite or copper sulfate. According to the invention, the electrolyte, the corrosion inhibitor and the additive are matched with one another, so that the corrosion amount can be accurately controlled, and the problem that forged aluminum is easy to have different-color marks after an anode section is effectively improved; in addition, the electrochemical polishing method provided by the invention is simple and suitable for large-scale application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of surface treatment technology and relates to an electrochemical polishing electrolyte and an electrochemical polishing method. Background Technology

[0002] With the trend towards thinner, lighter, and higher-performance consumer electronics (3C) products, aluminum has become a core material for casing manufacturing due to its excellent properties such as lightweight, corrosion resistance, and high strength. In traditional processes, aluminum materials require multiple CNC milling operations (a precision manufacturing technology that uses computer-controlled milling machines to process metal or non-metal materials) to be processed from raw sheet metal into finished casings. This not only results in a large amount of aluminum material being wasted, leading to low raw material utilization, but also significantly extends the production cycle due to the multiple processing steps, making it difficult to meet the mass production demands of rapid iteration in 3C products.

[0003] To overcome this limitation, forging technology has been gradually introduced into the manufacturing process of aluminum casings for 3C products. This technology applies external force to aluminum through a mold to achieve plastic deformation, enabling rapid mass production of blanks close to the finished product shape. This significantly reduces subsequent CNC machining, improving material utilization, shortening process time, and significantly reducing production costs. However, the forged aluminum needs heat treatment to eliminate processing stress and optimize mechanical properties. This process presents new challenges for subsequent surface treatment: after anodizing, heat-treated forged aluminum is prone to "frame imprint" defects. This defect manifests as discolored marks resembling the edge of a picture frame, which is particularly noticeable on light-colored casings, severely affecting the product's appearance quality and becoming a key bottleneck restricting the large-scale application of forged aluminum in the 3C field.

[0004] Traditional chemical polishing processes involve significant corrosion before anodizing, which can expose microscopic defects on the surface of forged aluminum, further exacerbating the appearance of "frame marks" after anodizing. While existing electrochemical polishing techniques for aluminum alloys can improve surface gloss and uniformity to some extent, they are insufficient to effectively address the "frame mark" problem in forged aluminum.

[0005] For example, the aluminum alloy electrolytic polishing slurry disclosed in patent CN101935863A improves polishing stability by adding aluminum and surfactants, but its core is to solve problems such as graying and pitting on the surface after polishing. It does not consider the problem of inconsistent local corrosion rates caused by microstructure differences after heat treatment of forged aluminum. Moreover, it relies on surfactants to improve the performance of the polishing slurry, but surfactants may increase the difficulty of wastewater treatment and increase the complexity of the process. Although the chromium-free electropolishing slurry proposed in patent CN106757298A achieves environmental protection, its high sulfuric acid content formula may aggravate selective corrosion on the surface of forged aluminum and amplify microstructure differences, which may aggravate the "frame mark".

[0006] Therefore, developing a method that can precisely control the amount of corrosion through electrochemical polishing technology, adapt to the characteristics of forged aluminum, and thus effectively improve the "frame print" has become an urgent need in the field of aluminum shell manufacturing for 3C products. Summary of the Invention

[0007] To address the shortcomings of existing technologies, the present invention aims to provide an electrochemical polishing electrolyte and an electrochemical polishing method. The electrochemical polishing electrolyte provided by this invention, with its electrolyte, corrosion inhibitor, and additives working in tandem, allows for precise control of the corrosion rate, thereby effectively improving the problem of "frame stains." Furthermore, the electrochemical polishing method provided by this invention is simple and suitable for large-scale application.

[0008] To achieve this objective, the present invention adopts the following technical solution:

[0009] In a first aspect, the present invention provides an electrochemical polishing electrolyte, the electrochemical polishing electrolyte comprising an electrolyte, a corrosion inhibitor, an additive, and a solvent, wherein the additive comprises any one or a combination of at least two of ethylene glycol, saccharin, sodium nitrite, or copper sulfate.

[0010] In this invention, the electrolyte enables the metal surface to corrode the highest points of the material surface under acidic conditions, reducing surface roughness and improving gloss to achieve the target value required by the anolyte. The corrosion inhibitor slows down the corrosion rate of the electrolyte on the material, allowing the electrolyte to react more evenly on the metal substrate. Without the corrosion inhibitor, the reaction would be too rapid and difficult to control. In addition, the corrosion inhibitor also prevents bubble formation, maintaining the stability of the electrolyte. The additive improves the surface texture of the polished material, preventing defects such as pores. The solvent dissolves and dilutes the electrolyte, corrosion inhibitor, and additive to form a uniform electrolyte. Through the synergistic effect of the electrolyte, corrosion inhibitor, additive, and solvent, the electrolyte not only has excellent polishing effect but also good stability.

[0011] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. The technical objectives and beneficial effects of the present invention can be better achieved and realized through the following preferred technical solutions.

[0012] Preferably, the electrolyte comprises any one or a combination of at least two of sulfuric acid, oxalic acid, tartaric acid, citric acid, boric acid, or phosphoric acid.

[0013] Preferably, the total concentration of the electrolyte in the electrochemical polishing electrolyte is 1200 g / L to 1600 g / L, such as 1200 g / L, 1300 g / L, 1400 g / L, 1450 g / L, 1500 g / L or 1600 g / L, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0014] Preferably, the electrolyte is a combination of at least two of oxalic acid, tartaric acid, citric acid, boric acid, or phosphoric acid, and more preferably a combination of phosphoric acid and oxalic acid.

[0015] Preferably, the mass ratio of phosphoric acid to oxalic acid is (5-7):1, such as 5:1, 5.5:1, 6:1, 6.5:1 or 7:1, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0016] In this invention, phosphoric acid, as a strong acidic complexing agent, is mainly responsible for dissolving the oxide layer on the metal surface and maintaining the viscosity of the electrolyte, thus promoting surface smoothing. Oxalic acid, as a weak acidic organic carboxylic acid, possesses both corrosion inhibition and complexing capabilities, which can regulate the corrosion rate and help stabilize metal ions. Sulfuric acid, on the other hand, is a strong acid and easily leads to localized over-corrosion. Therefore, when using a combination of acids other than sulfuric acid, and further selecting a combination of phosphoric acid and oxalic acid, it is more beneficial to control the corrosion rate and effectively improve the "frame mark". At the same time, the mass ratio of phosphoric acid to oxalic acid also affects the polishing effect. When it is controlled within the above-mentioned preferred range, the brightness and uniformity of the metal surface can be better balanced.

[0017] Preferably, the corrosion inhibitor comprises any one or a combination of at least two of triethanolamine, thiourea, urea, glycerol, propanol or butanol, and more preferably glycerol.

[0018] Preferably, the concentration of the corrosion inhibitor in the electrochemical polishing electrolyte is 1 g / L to 5 g / L, such as 1 g / L, 2 g / L, 3 g / L, 4 g / L or 5 g / L, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0019] In this invention, glycerol molecules have a large number of hydroxyl groups, which can form multi-point adsorption with the metal surface through hydrogen bonds, thus constructing a denser and more uniform adsorption film on the metal surface. This allows for more uniform adjustment of the corrosion rate in different areas and reduces local unevenness in gloss caused by differences in structure. Furthermore, glycerol has a higher viscosity and boiling point, making it more stable during electrochemical polishing. In addition, the concentration of the corrosion inhibitor in the electrolyte should not be too high, otherwise it will affect the polishing efficiency.

[0020] Preferably, the additive is sodium nitrite.

[0021] In this invention, when sodium nitrite is selected as an additive, it can inhibit excessive dissolution in acidic environments, protect pores and fine structures, and thus exhibit better polishing effects.

[0022] Preferably, the concentration of the additive in the electrochemical polishing electrolyte is 0.5 g / L to 3 g / L, for example, 0.5 g / L, 1 g / L, 1.5 g / L, 2 g / L, 2.5 g / L or 3 g / L, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0023] Preferably, the solvent includes water.

[0024] Preferably, the electrochemical polishing electrolyte also includes Al. 3+ .

[0025] Preferably, the Al 3+ Its sources include elemental aluminum.

[0026] Preferably, the elemental aluminum comprises any one or a combination of at least two of aluminum sheets, aluminum wires, or aluminum powder, and more preferably aluminum wires.

[0027] It should be noted that AI 3+ Aluminum salts are generally not used as the source of the reaction because they may introduce other impurity ions, causing uncontrollable effects on the reaction process. Furthermore, when Al... 3+ When the source of the oxidant is elemental aluminum, the presence of acid in the electrolyte will oxidize the elemental aluminum to Al. 3+ Furthermore, Al was introduced by adding aluminum wire. 3+ More efficient, the amount added only needs to be adjusted according to the volume of the bath. The concentration can be measured after aluminum is melted. If insufficient, aluminum can be melted again until the target Al is reached. 3+ Concentration value.

[0028] Preferably, the Al 3+ The concentration is 6 g / L to 35 g / L, such as 6 g / L, 10 g / L, 12 g / L, 15 g / L, 20 g / L, 24 g / L, 30 g / L or 35 g / L, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0029] In this invention, Al is introduced before electrochemical polishing. 3+ By controlling its concentration within the aforementioned preferred range, a better balance can be struck between the corrosion rate and leveling properties of the material, which is more conducive to reducing the defect of "frame imprint". If the electrolyte does not contain Al 3+ If the polishing effect is not ideal, the surface may appear white and hazy; and if the Al in the electrolyte is not ideal... 3+ If the concentration is too high, due to Al 3+ Accumulation increases the viscosity of the solution, which is not conducive to the leveling of the polishing slurry on the workpiece surface. Instead, it reduces the polishing efficiency and increases the risk of surface pitting.

[0030] It should be noted that this invention does not limit the preparation method of the electrolyte; commonly used methods in the art for preparing electrochemical polishing electrolytes are applicable to this invention. Exemplarily, this invention provides a preparation method: first, the electrolyte is dissolved in a solvent, then additives and corrosion inhibitors are added sequentially, and finally elemental aluminum is added. This method is more conducive to the uniform dissolution of the electrolyte, additives, and corrosion inhibitors in the solvent.

[0031] In a second aspect, the present invention also provides a method for electrochemical polishing, the method comprising: electrochemically polishing a substrate using an electrochemical polishing electrolyte as described in the first aspect.

[0032] Preferably, the bias voltage for electrochemical polishing is 3V to 12V, such as 3V, 5V, 6V, 9V, 10V or 12V, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0033] In this invention, when the bias voltage of electrochemical polishing is within the above-mentioned preferred range, the degree of corrosion of grain boundaries and craters is moderate, and the amount of metal erosion and weight loss is small.

[0034] Preferably, the temperature during the electrochemical polishing process is 72℃~78℃, such as 72℃, 73℃, 74℃, 75℃, 76℃, 77℃ or 78℃, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0035] Preferably, before the electrochemical polishing, the substrate is sequentially degreased and neutralized, and after the degreasing and neutralization treatments, each is independently washed with water.

[0036] Preferably, after the electrochemical polishing, the product is sequentially subjected to water washing, neutralization, anodizing, surface conditioning, dyeing, sealing and baking, and water washing is performed independently after each of the neutralization, anodizing, surface conditioning, dyeing and sealing processes.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] In this invention, the electrolyte, corrosion inhibitor, and additives work together to precisely control the amount of corrosion, thereby effectively improving the problem of "frame marks." Furthermore, the electrochemical polishing method provided by this invention is simple and suitable for large-scale application. Attached Figure Description

[0039] Figure 1 This is a schematic diagram illustrating the principle of the electrochemical polishing method provided in Example 1.

[0040] Figure 2These are surface state diagrams of aluminum alloy plate parts in Examples 1, 10, 11, Comparative Examples 3, 5, and 6 under the same polishing time.

[0041] Figure 3 These are surface state diagrams of the aluminum alloy plate parts in Examples 1 and 12-14 under the same polishing time.

[0042] Figure 4 These are crystal phase diagrams of the aluminum alloy plate parts in Examples 1 and 9-11 under the same polishing time.

[0043] Figure 5 These are crystal phase diagrams of the aluminum alloy plate parts in Example 1 and Comparative Example 3 under the same polishing time.

[0044] Figure 6 This is a schematic diagram of regions A, B, and C of the aluminum alloy plate parts used in Examples 1-14 and Comparative Examples 1-7.

[0045] Figure 1 In the middle: 1-Cathode; 2-Specimen; 3-Glass rod; 4-Electrolyte; Figure 6 In the middle: A refers to the middle area of ​​the aluminum alloy plate part, B refers to the area of ​​the aluminum alloy plate part 1cm to 3cm from the side, and C refers to the area of ​​the aluminum alloy plate part within 1cm from the side. The red line area is where the frame print is likely to appear. Detailed Implementation

[0046] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0047] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.

[0048] Example 1

[0049] This embodiment provides a method for electrochemical polishing of aluminum alloy sheet parts. The principle diagram of this method is shown below. Figure 1 As shown, 1 is the cathode, 2 is the specimen, 3 is the glass rod, and 4 is the electrolyte. The electrolyte consists of electrolyte, corrosion inhibitor, additives, and Al. 3+The composition includes a solvent, wherein the electrolyte is a combination of phosphoric acid and oxalic acid at concentrations of 1250 g / L and 200 g / L, respectively; the corrosion inhibitor is glycerol at a concentration of 3 g / L; the additive is sodium nitrite at a concentration of 1 g / L; and the solvent is water. 3+ The concentration is 24 g / L. The specific method is as follows:

[0050] (1) Weigh phosphoric acid, oxalic acid, glycerol, and water according to the composition of the electrolyte. First, pour the phosphoric acid and oxalic acid into a container, add deionized water and stir until completely dissolved. Then, add sodium nitrite and stir until completely dissolved. Finally, slowly add glycerol and raise the temperature to 75°C. After stabilization, add aluminum wire to make the Al in the electrolyte... 3+ When the concentration reaches 24 g / L, the preparation of the electrochemical polishing electrolyte is complete.

[0051] (2) The aluminum alloy plate parts are degreased and neutralized in sequence, and washed with water after each step;

[0052] (3) At 75°C, the bias voltage is set to 6V, and then the treated aluminum alloy plate parts are subjected to electrochemical polishing.

[0053] (4) The aluminum alloy plate parts obtained in step (3) are subjected to neutralization, anodizing, surface conditioning, dyeing and sealing treatment in sequence. After each step, they are washed with water and finally baked at 80°C for 25 minutes to obtain the product.

[0054] Example 2

[0055] This embodiment provides a method for electrochemical polishing of aluminum alloy plate parts. The electrolyte consists of electrolyte, corrosion inhibitor, additives, and Al. 3+ The composition includes a solvent, wherein the electrolyte is a combination of phosphoric acid and citric acid at concentrations of 1000 g / L and 200 g / L, respectively; the corrosion inhibitor is glycerol at a concentration of 1 g / L; the additive is sodium nitrite at a concentration of 0.5 g / L; and the solvent is water. 3+ The concentration is 24 g / L. The specific method is as follows:

[0056] In step (1), the temperature is raised to 72°C and aluminum wire is added after it stabilizes. Step (3) is also carried out at 72°C. The remaining preparation methods and parameters are consistent with those in Example 1.

[0057] Example 3

[0058] This embodiment provides a method for electrochemical polishing of aluminum alloy plate parts. The electrolyte consists of electrolyte, corrosion inhibitor, additives, and Al. 3+The composition includes a solvent, wherein the electrolyte is a combination of phosphoric acid and oxalic acid at concentrations of 1400 g / L and 200 g / L, respectively; the corrosion inhibitor is glycerol at a concentration of 5 g / L; the additive is sodium nitrite at a concentration of 3 g / L; and the solvent is water. 3+ The concentration was 24 g / L.

[0059] In step (1), the temperature is raised to 78°C and aluminum wire is added after it stabilizes. Step (3) is also carried out at 78°C. The remaining preparation methods and parameters are consistent with those in Example 1.

[0060] Example 4

[0061] The difference between this embodiment and Embodiment 1 is that, in this embodiment, the concentration of oxalic acid is 100 g / L;

[0062] The remaining preparation methods and parameters are consistent with those in Example 1.

[0063] Example 5

[0064] The difference between this embodiment and Embodiment 1 is that, in this embodiment, the corrosion inhibitor is triethanolamine;

[0065] The remaining preparation methods and parameters are consistent with those in Example 1.

[0066] Example 6

[0067] The difference between this embodiment and Embodiment 1 is that, in this embodiment, the corrosion inhibitor is glycerol;

[0068] The remaining preparation methods and parameters are consistent with those in Example 1.

[0069] Example 7

[0070] The difference between this embodiment and Embodiment 1 is that in this embodiment, the concentration of the corrosion inhibitor is 10 g / L;

[0071] The remaining preparation methods and parameters are consistent with those in Example 1.

[0072] Example 8

[0073] The difference between this embodiment and Embodiment 1 is that, in this embodiment, the additive is copper sulfate;

[0074] The remaining preparation methods and parameters are consistent with those in Example 1.

[0075] Example 9

[0076] The difference between this embodiment and Embodiment 1 is that, in this embodiment, the electrolyte does not contain Al. 3+ No aluminum wire is added in step (1);

[0077] The remaining preparation methods and parameters are consistent with those in Example 1.

[0078] Example 10

[0079] The difference between this embodiment and Embodiment 1 is that, in this embodiment, the Al in the electrolyte... 3+ The concentration was 12 g / L;

[0080] The remaining preparation methods and parameters are consistent with those in Example 1.

[0081] Example 11

[0082] The difference between this embodiment and Embodiment 1 is that, in this embodiment, the Al in the electrolyte... 3+ The concentration was 35 g / L;

[0083] The remaining preparation methods and parameters are consistent with those in Example 1.

[0084] Example 12

[0085] The difference between this embodiment and embodiment 11 is that in this embodiment, the bias voltage is set to 3V in step (3);

[0086] The remaining preparation methods and parameters are consistent with those in Example 11.

[0087] Example 13

[0088] The difference between this embodiment and embodiment 11 is that in this embodiment, the bias voltage is set to 9V in step (3);

[0089] The remaining preparation methods and parameters are consistent with those in Example 11.

[0090] Example 14

[0091] The difference between this embodiment and embodiment 11 is that in this embodiment, the bias voltage is set to 12V in step (3);

[0092] The remaining preparation methods and parameters are consistent with those in Example 11.

[0093] Comparative Example 1

[0094] The difference between this comparative example and Example 1 is that the electrolyte in this comparative example does not contain any additives.

[0095] The remaining preparation methods and parameters are consistent with those in Example 1.

[0096] Comparative Example 2

[0097] The difference between this comparative example and Example 1 is that in this comparative example, the additive is a combination of magnesium sulfate and isopropanol.

[0098] The remaining preparation methods and parameters are consistent with those in Example 1.

[0099] Comparative Example 3

[0100] The difference between this comparative example and Example 1 is that in this example, the bias voltage is set to 0V in step (3);

[0101] The remaining preparation methods and parameters are consistent with those in Example 1.

[0102] Comparative Example 4

[0103] The difference between this comparative example and Example 9 is that in this example, the bias voltage is set to 0V in step (3);

[0104] The remaining preparation methods and parameters are consistent with those in Example 9.

[0105] Comparative Example 5

[0106] The difference between this comparative example and Example 10 is that in this example, the bias voltage is set to 0V in step (3);

[0107] The remaining preparation methods and parameters are consistent with those in Example 10.

[0108] Comparative Example 6

[0109] The difference between this comparative example and Example 11 is that in this example, the bias voltage is set to 0V in step (3);

[0110] The remaining preparation methods and parameters are consistent with those in Example 11.

[0111] Comparative Example 7

[0112] This comparative example provides a method for chemical polishing aluminum alloy sheet parts, wherein the electrolyte consists of an electrolyte and Al. 3+ The solution consists of a solvent and an electrolyte, wherein the electrolyte is a combination of phosphoric acid and sulfuric acid with concentrations of 1250 g / L and 200 g / L, respectively, a phosphorus-to-sulfur ratio of 6.5:1, a density ratio of phosphoric acid to sulfuric acid in the solution of 1.76, and water as the solvent. 3+ The concentration is 22 g / L. The polishing process involves immersing the aluminum alloy plate parts in this chemical polishing electrolyte.

[0113] Performance testing

[0114] Using the methods in Examples 1-14 and Comparative Examples 1-7, aluminum alloy sheet parts were polished to the same gloss. The amount of etch and weight loss before and after polishing are shown in Table 1 below.

[0115] Using the methods described in Examples 1, 10, 11, and Comparative Examples 3, 5, and 6, the aluminum alloy sheet parts were polished for the same amount of time, and the surface condition of the materials was photographed using Keyence cameras. Figure 2 As shown.

[0116] Using the methods described in Examples 1 and 12-14, the aluminum alloy sheet parts were polished for the same amount of time, and the surface condition of the material was photographed using Keyence cameras, such as... Figure 3 As shown.

[0117] Using the methods in Examples 1, 9-11, and Comparative Example 1, the aluminum alloy plate parts were polished for the same amount of time, and the crystal phase structure of the material was characterized. The results are as follows: Figure 4 and Figure 5 As shown.

[0118] Table 1

[0119]

[0120]

[0121] As can be seen from the comparison of the data of Example 1 with Comparative Examples 1 and 2 in Table 1, the addition of additives in the electrochemical polishing electrolyte is necessary, and the type of additives also has an important impact on the amount of erosion and weight loss of the material. As can be seen from the comparison of the data of Example 1 with Comparative Example 7 in Table 1, when polishing aluminum alloy plate parts to the same gloss, the amount of erosion and weight loss are significantly reduced by electrochemical polishing compared with traditional chemical polishing.

[0122] Combined with Examples 1, 12-14, and Comparative Examples 3-6 in Table 1 Figure 2 , Figure 3 , Figure 5 and Figure 6 It can be seen that applying a bias voltage during the polishing process can reduce corrosion of grain-related features (grain boundaries, grains), maintaining a smoother surface. Furthermore, the higher the applied bias voltage, the less noticeable the grain boundary corrosion. Simultaneously, the higher the applied bias voltage, the lower the amount of erosion and weight loss, but the crater corrosion becomes more severe. The crater corrosion in material region C (1 cm from the side edge) is more severe than in regions A (middle region) and B (1-3 cm from the side edge). This is consistent with Examples 1 and 9-11 in Table 1. Figure 2 and Figure 4 It can be seen that with the increase of aluminum ion concentration, the amount of etching, weight loss, and degree of grain boundary corrosion all show a trend of first decreasing and then increasing, while the corrosion degree of the crater shows the opposite trend, showing a trend of first increasing and then decreasing. This application uses Al 3+When the concentration is controlled between 6 g / L and 35 g / L and the bias voltage is controlled between 3 V and 12 V, the overall performance of the material is at a relatively good level. However, if it is not within this range, one aspect of the material's performance will decline, which is not conducive to improving the overall performance of the material.

[0123] A comparison of the data from Examples 1 and 4-8 shows that, in this application, the ratio of phosphoric acid to oxalic acid, the types of corrosion inhibitors and additives, and the concentration of corrosion inhibitors in the electrochemical polishing electrolyte all affect the electrochemical polishing process. By controlling these within the preferred ranges of this application, both the amount of etching and the weight loss can be kept at a low level.

[0124] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. An electrochemical polishing electrolyte, characterized in that, The electrochemical polishing electrolyte includes an electrolyte, a corrosion inhibitor, an additive, and a solvent. The additive includes any one or a combination of at least two of ethylene glycol, saccharin, sodium nitrite, or copper sulfate.

2. The electrochemical polishing electrolyte according to claim 1, characterized in that, The electrolyte includes any one or a combination of at least two of sulfuric acid, oxalic acid, tartaric acid, citric acid, boric acid, or phosphoric acid; Preferably, the total concentration of the electrolyte in the electrochemical polishing electrolyte is 1200 g / L to 1600 g / L.

3. The electrochemical polishing electrolyte according to claim 2, characterized in that, The electrolyte is a combination of at least two of oxalic acid, tartaric acid, citric acid, boric acid, or phosphoric acid, and more preferably a combination of phosphoric acid and oxalic acid; Preferably, the mass ratio of phosphoric acid to oxalic acid is (5-7):

1.

4. The electrochemical polishing electrolyte according to any one of claims 1-3, characterized in that, The corrosion inhibitor includes any one or a combination of at least two of triethanolamine, thiourea, urea, glycerin, propanol or butanol, and is more preferably glycerin; Preferably, the concentration of the corrosion inhibitor in the electrochemical polishing electrolyte is 1 g / L to 5 g / L.

5. The electrochemical polishing electrolyte according to any one of claims 1-4, characterized in that, The additive is sodium nitrite; Preferably, the concentration of the additive in the electrochemical polishing electrolyte is 0.5 g / L to 3 g / L.

6. The electrochemical polishing electrolyte according to any one of claims 1-5, characterized in that, The solvent includes water.

7. The electrochemical polishing electrolyte according to any one of claims 1-6, characterized in that, The electrochemical polishing electrolyte also includes Al. 3+ ; Preferably, the Al 3+ The concentration ranges from 6 g / L to 35 g / L.

8. A method for electrochemical polishing, characterized in that, The method includes: electrochemically polishing the substrate using the electrochemical polishing electrolyte as described in any one of claims 1-7.

9. The method according to claim 8, characterized in that, The bias voltage for the electrochemical polishing is 3V to 12V; Preferably, the temperature during the electrochemical polishing process is 72°C to 78°C.

10. The method according to claim 8 or 9, characterized in that, Prior to the electrochemical polishing, the substrate is sequentially degreased and neutralized, and after the degreasing and neutralization treatments, each is independently washed with water. Preferably, after the electrochemical polishing, the product is sequentially subjected to water washing, neutralization, anodizing, surface conditioning, dyeing, sealing and baking, and water washing is performed independently after each of the neutralization, anodizing, surface conditioning, dyeing and sealing processes.

Citation Information

Patent Citations

  • Aluminum alloy electrolytic polishing solution, preparation method and aluminum alloy electrolytic polishing method

    CN101935863A

  • Chromium-free electropolishing solution, method for electropolishing of aluminum alloy and automotive aluminum decoration part

    CN106757298A